Ureterocele in Combination with Urolithiasis in a Pregnant Woman - Khairli, Gafur; Zhanbyrbekuly, Ulanbek; Suchshenko, Alexey; Muralovich Kazhitaev, Almas; Zulfugarogly Alnagiev, Ravshan; Alyshanogly Ismailov, Orkhan; Dulatuly Akhmetkhan, Darkhan; Zhakiyauly Baigozha, Abylaikhan (West Kazakhstan Medical Journal, 2023)
This article is devoted to the description of the clinical picture, methods of laboratory and instrumental diagnostics, the choice of surgical treatment and postoperative rehabilitation of a patient with a rare urological pathology - ureterocele in combination with urolithiasis in a pregnant woman.